Molar Incisor Hypomineralization in adolescents and adults and its association with facial profile and occlusion - Hanan, Simone Assayag [UNESP]; de Farias, Aline Leite [UNESP]; Santos-Pinto, Lourdes [UNESP] (Springer Nature, 2023)
Objectives: To date, there are no data available in the scientific literature about the diagnosis of Molar Incisor Hypomineralization (MIH) in adults. We aimed to assess the MIH prevalence and clinical characteristics in adolescents and adults and its association with facial profile and occlusion. Materials and methods: In this cross-sectional study, permanent teeth were evaluated in 275 patients between the ages of 12 and 49 at a dental clinic, using intraoral photographs. A calibrated examiner classified enamel hypomineralization using the MIH index. Statistical analyses were performed using chi-square, Fisher’s tests, and ordinal logistic regression. Results: MIH was observed in 12.73% of all patients. The most commonly affected teeth were permanent molars, while incisors, premolars, and canines were less affected. MIH usually appears as demarcated opacities, with less than one-third of the tooth affected. There was no association between severe defects and facial profile and occlusion, but rather with the higher age of the participants. Conclusion: Enamel hypomineralization mainly affects the first and second permanent molars, but it could also be observed in the third molars, although it is not associated with the orthodontic characteristics investigated. Clinical relevance: This is the first study to highlight the prevalence of MIH in adults. This result showed the importance of other specialists beyond Pediatric Dentistry in the diagnosis of this defect. In addition, hypomineralization of other permanent teeth (canines, premolars, and second molars) has been described previously in other studies, but this is the first to identify MIH in third molars.
Keywords: Dental enamel; Facial profile; Hypomineralization; Malocclusion; Prevalence